RESPON PASANGAN USIA SUBUR TERHADAP PROGRAM KELUARGA BERENCANA GRATIS di KELURAHAN DELIMA KECAMATAN TAMPAN - Mariya Ulfa; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research of this free family planning programs, intend to know how response of fertile age couple to free family planning programs and any kind factors to influence the response. The location of this research at Puskesmas RI Sidomulyo Delima district of Tampan. Method that used is kuantative method with descrptive analysis, that is obtained data collecting based on the fact in field by spreading enquette, interview, and documentation. Responder of this research consist 96 fertile age couple. The framework of teory is response teory, and participation teory. The result of research response fertile age couple to free family planning programs at Delima is positive, proven 63 from 96 responder have used family planning program. This matter supported by participation of husband and sosialitation from family palnning officer in Delima. Factors influence of respons that is education, work, involvement of closest person, and culture, economic, religion condition.Key word : Respons, Fertile age couple, Free family planning program